MORPHOLOGICAL FEATURES OF LUNG STRUCTURE AND FUNCTIONAL ACTIVITY OF THE AIRWAYS OF GUINEA PIGS AFTER LONG-TERM EXPOSURE WITH NANOSIZED MAGNETITE A - Ye. Ye. Abramenko; A. V. Nosarev; L. V. Smaglyi; L. V. Kapilevich; Ye. Yu. D’yakova; A. M. Tabayeva; T. A. Kironenko; V. S. Selivanova (Бюллетень сибирской медицины)
The results of study, in which we examined the influence of nanosized magnetite on breath organs histological structure and contractility activity of the airways of guinea pigs by method of mechanography has been presented. In the lungs of experimental animals an inflammatory response developed as a result of long-term inhalation intake of nanosized magnetite. Also the functional status of the airways changed and appeared as changing of amplitude of contractility response under the action of histamine.